CUSTOMER CHURN PREDITION IN TELECOM SECTOR USING SUPPORT VECTOR MACHINE - K.SOWMYA, DR.R.VIJAYARAJESWARI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Acquisition and retention of new clients are one of the most significant concerns of businesses. While recipient companies concentrate on acquiring new customers, mature ones try to focus on retention of the existing ones in order to provide themselves with the opportunity of cross – selling. According to Freeman (1999) one of the most significant ways of increasing customers’ value is to keep them for longer period of time.